Al-Ghazali's Thought-Based Moral Education Innovation in Responding to the Moral Crisis of Generation Z - Fadhilatul Auliya; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of digital technology has brought major changes in the lives of Generation Z, including in the way they think, behave, and behave. On the other hand, this change also raises various moral problems that show that technological and knowledge advances are not always followed by moral and spiritual maturity. Departing from these conditions, this study aims to examine the concept of moral education in Al Ghazali's thought and examine its relevance in responding to the moral crisis of Generation Z in the digital era. This research uses a qualitative approach through library research. Data was obtained from primary sources in the form of Al-Ghazali's works and supported by various secondary literature that discusses moral education, characteristics of Generation Z, and educational challenges in the digital era. Data analysis was carried out using content analysis techniques to understand the main idea of Al-Ghazali's moral education and relate it to the reality of today's education. The results of the study show that moral education according to Al-Ghazali emphasizes the process of inner development through purification of the soul (tazkiyat al-nafs), balance between knowledge and practice, habituation of good behavior, and the importance of the role model of educators. These principles are still very relevant to be applied in the education of Generation Z, especially in the face of the negative influence of digitalization which tends to form an instant attitude and weaken moral control. This research offers novelty value by associating Al-Ghazali's moral education thinking with the context of Generation Z's life in the digital era. These findings show that Al-Ghazali's classical thought is not obsolete, but can be developed contextually through the integration of Islamic moral values with modern learning media and methods, thus remaining relevant and applicable without losing its spiritual dimension.